Extra-adrenal adrenocortical cancer associated with multiple endocrine neoplasia type 1 - Deirdre Green; Kate Richards; Brendan Doyle; Chris Thompson; Arnold Hill; Michael W O’Reilly; Mark Sherlock (Endocrinology, Diabetes & Metabolism Case Reports)
Adrenocortical carcinoma (ACC) is a rare malignant tumour arising from the adrenal cortex, with an estimated annual incidence of one to two patients per million. Ectopic ACCs are extremely rare. The majority of ACCs are sporadic; however, ACC has been linked with genetic disease processes, including multiple endocrine neoplasia type-1 (MEN-1). We present the case of a 66-year-old lady referred with newly diagnosed diabetes on a background of primary hyperparathyroidism. Examination revealed Cushingoid features, and hormonal evaluation confirmed ACTH-independent Cushing’s syndrome. Morning cortisol after a 1 mg overnight dexamethasone suppression test was 548 nmol/L with an undetectable ACTH <3.0 pg/mL. Dehydroepiandrosterone sulphate was 5.3 μmol/L and androstenedione 3.49 nmol/L, both of which were normal. Testosterone was suppressed at <0.4 nmol/L. Imaging revealed a 6 × 6 × 4.5 cm right-sided presumed adrenal lesion, a pancreatic lesion (2.5 × 1.6 cm), and bilateral pulmonary nodules (0.9 × 0.8 cm, 0.7 × 0.6 cm, 0.3 cm). Right adrenalectomy was performed, and histology was consistent with an extra-adrenal ACC (Weiss score 5/9) within the peri-adrenal adipose tissue. The resected adrenal gland was normal. Lung biopsy confirmed metastatic ACC tissue, and endoscopic ultrasound-guided biopsy of the pancreatic lesion revealed a pancreatic neuroendocrine tumour, which was confirmed biochemically to be an insulinoma. Genetic assessment confirmed MEN-1. This case highlights the importance of screening for MEN-1 in at-risk patients and the need for close clinical follow-up. To our knowledge, this is the first case report of extra-adrenal ACC in MEN-1 syndrome.